System Maid Online as Violations of the MoU on Placement and Protection of Indonesian Migrant Workers in the Domestic Sector in Malaysia 2022 - Saepudin; Revidy, Aldebaran Raihan; Mustofa, Syifa Aulia Al (Veteran Law Review, 2024)
This research discusses in depth Malaysia's non-compliance with the Memorandum of Understanding (MoU) on the placement and protection of Indonesian Migrant Workers in the Domestic Sector (PMID) in Malaysia in 2022, through the continued use of System Maid Online (SMO) in the PMID recruitment process. A normative legal research method with a conceptual approach is used, supported by secondary data sources from previous research such as journal articles, books, and mainstream media. The principles of Pacta Sunt Servanda and Good Faith in international treaty law are used as analytical tools in this research. This research also argues that the MoU has legally binding and Malaysia's delay in providing One Channel System (OCS) in PMID recruitment has violated the principles of Pacta Sunt Servanda and Good Faith stipulated in Article 26 of the 1969 Vienna Convention. Indonesia then responded to this problem with a temporary moratorium on sending PMI, which indicates the importance of implementing international agreements and the obligation to respect international agreements. Furthermore, this study also suggests that Indonesia maximizes its diplomatic capacities to increase Indonesia's bargaining position and pressure Malaysia to be serious in protecting the rights of migrant workers.